2002
DOI: 10.1103/physrevb.65.134502
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a Josephson array in a resonant cavity

Abstract: We derive dynamical equations for a Josephson array coupled to a resonant cavity by applying the Heisenberg equations of motion to a model Hamiltonian described by us earlier [Phys. Rev. B 63, 144522 (2001); Phys. Rev. B 64, 179902 (E)]. By means of a canonical transformation, we also show that, in the absence of an applied current and dissipation, our model reduces to one described by Shnirman et al [Phys. Rev. Lett. 79, 2371(1997] for coupled qubits, and that it corresponds to a capacitive coupling between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 44 publications
4
59
0
1
Order By: Relevance
“…The main criteria for the high detected ac power output was a sharp resonance of the cavity and a coupling mechanism between the cavity and the individual JJs. Subsequent theoretical work by Almaas and Stroud 32,33 resulted in dynamical equations for JJ arrays coupled to a resonant cavity that reproduced well the experimental data of Barbara and co-workers. In this model, Almaas and Stroud showed that the effective coupling resulting in the coherent emission of radiation could be thought of as a capacitive coupling between the charge variables of the junctions and the cavity.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…The main criteria for the high detected ac power output was a sharp resonance of the cavity and a coupling mechanism between the cavity and the individual JJs. Subsequent theoretical work by Almaas and Stroud 32,33 resulted in dynamical equations for JJ arrays coupled to a resonant cavity that reproduced well the experimental data of Barbara and co-workers. In this model, Almaas and Stroud showed that the effective coupling resulting in the coherent emission of radiation could be thought of as a capacitive coupling between the charge variables of the junctions and the cavity.…”
supporting
confidence: 54%
“…Our work is based on an approach similar to that of Ref. 32. We construct a Hamiltonian describing a serial array of N underdamped JJs coupled to a dilatational AlN oscillator.…”
mentioning
confidence: 99%
“…As we emphasize, both are of great interest in the light of current research in the fields of quantum computing and quantum-information processing [10][11][12][13]. Moreover, the results presented in this paper emphasize that the SQUID ring can act as a versatile quantum device and, as we have shown previously, can be used to create correlations across extended, multicomponent, quantum circuit systems [1,2,[30][31][32][33]. These correlations can, for example, be made manifest as quantum entanglements and quantum frequency up/down-conversion [1,2], with each controlled by the external bias flux applied to the SQUID ring.…”
Section: Discussionmentioning
confidence: 72%
“…If no soliton ͑i.e., no fluxon͒ is present, the junction behaves very much like a small Josephson junction. 9 In particular, there are SIRSs just as in a small junction, which occur at the voltages expected for a small junction.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] These models generally succeed in reproducing many of the salient features of the experiments: SIRSs at the expected voltage, and an increase in the energy in the cavity proportional to the square of the number of junctions. The models have now been extended to two-dimensional ͑2D͒ junction arrays, 12 where they show that, on a given step, the 2D arrays radiate much more energy into the cavity than the one-dimensional ͑1D͒ arrays.…”
Section: Introductionmentioning
confidence: 99%